Estimation and testing for varying coefficients in additive models with marginal integration - Lijian Yang; Byeong U. Park; Lan Xue; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
We propose marginal integration estimation and testing methods for the coefficients of varying coefficient multivariate regression model. Asymptotic distribution theory is developed for the estimation method which enjoys the same rate of convergence as univariate function estimation. For the test statistic, asymptotic normal theory is es- tablished. These theoretical results are derived under the fairly general conditions of absolute regularity (b-mixing). Application of the test procedure to the West Ger- man real GNP data reveals that a partially linear varying coefficient model is best parsimonious in fitting the data dynamics, a fact that is also confirmed with residual diagnostics.
Keywords: 330; Equivalent kernels; German real GNP; Local polynomial; Marginal integration; Rate of convergence; Schätztheorie; Statistischer Test; Regression; Sozialprodukt; Deutschland